BizTalk 2010 EDI for Health Care HIPAA Compliant 837 Solutions - Beckner, Mark. (Apress : Imprint: Apress, 2013)
Building a successful health care claims processing EDI implementation in BizTalk Server can be complex. Decisions must be made around how to extract and publish data, how to map to the 837 EDI standard, and how to appropriately batch and deliver data. If architected properly, your BizTalk solution can be highly efficient, simple, and something that can be managed and extended for years to come. The topics in this book include building complete inbound and outbound solutions for 837 Institutional and Professional EDI document types. In addition, topics around 997/999 acknowledgements and related document types are included. Covering mapping, trading partner configuration, AS2, SFTP, data extraction, data routing, and batching, you will find this to be a goldmine of information to aid you in a successful implementation.